PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN CARD MATCHING GAME TERHADAP AKTIVITAS BELAJAR SISWA PADA MATERI IPA KELAS VIII MTS MA’ARIF AMBULU - Abdul Rahim; Khoirun Nisa' (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze the effect of the Discovery Learning learning model assisted by Card Matching Game media on student learning activities in science material for grade VIII at MTs Ma'arif Ambulu. The study used a quantitative approach with a quasi-experimental design and a posttest-only nonequivalent control group design . The study sample consisted of 45 grade VIII students divided into an experimental class (n = 24) who received Discovery Learning learning assisted by Card Matching Game and a control class (n = 21) who received conventional learning. Learning activity data were collected through observation sheets that had been tested for validity through expert judgment and declared reliable, then analyzed using the Shapiro-Wilk normality test, Levene's Test homogeneity test , and Independent Sample T-Test at a significance level of 5%. The results of the descriptive analysis showed that the average learning activity of the control class was 28.93 and the experimental class was 28.69, with the experimental class showing a more homogeneous data distribution (SD = 2.221) compared to the control class (SD = 4.950). The results of the hypothesis test obtained a Sig. value. (2-tailed) of 0.839 (> 0.05), so H0 is accepted and H1 is rejected. This finding indicates that the implementation of Discovery Learning assisted by Card Matching Game has not provided a statistically significant effect on student learning activities, which is thought to be influenced by the limited duration of treatment, the equality of the initial abilities of both classes, and the stage of student adaptation to discovery-based learning. This result provides an empirical contribution that the effectiveness of a learning model needs to consider contextual factors, not merely the theoretical superiority of the model.